2005
DOI: 10.1002/ejlt.200401126
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation and hydroxlation of rubber seed oil: one‐pot multi‐step reactions

Abstract: Epoxidized and hydroxylated rubber seed oils were prepared by peroxyformic acid generated in situ by reacting formic acid and hydrogen peroxide with RSO, a renewable resource. The structural and physico-chemical properties of RSO have been determined. The fatty acid composition showed a high content of polyunsaturated fatty acids. The modified products were characterized with regard to their structure and properties. The findings of this study revealed that both hydroxylated and epoxidized RSO can be prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 14 publications
4
72
1
Order By: Relevance
“…In the current work, less OOC was obtained, which may be due to higher acid value of castor oil. Okieimen et al [45] observed similar results during their study on epoxidation of high acid value rubber seed oil. Hence, 60°C temperature was considered as suitable for epoxidation of CO, when molar ratio of unsaturation: acetic acid: hydrogen peroxide was 1:0.5:1.5 and catalysts loading 15 wt%.…”
Section: Influence Of Various Process Variables On Maximum Oocsupporting
confidence: 54%
“…In the current work, less OOC was obtained, which may be due to higher acid value of castor oil. Okieimen et al [45] observed similar results during their study on epoxidation of high acid value rubber seed oil. Hence, 60°C temperature was considered as suitable for epoxidation of CO, when molar ratio of unsaturation: acetic acid: hydrogen peroxide was 1:0.5:1.5 and catalysts loading 15 wt%.…”
Section: Influence Of Various Process Variables On Maximum Oocsupporting
confidence: 54%
“…Dioctyl phthalate (DOP) (Merck) (refractive index 1.4399 and density 0.993g/cm 3 ) was used as plasticizer. Epoxidized rubber seed oil (ERSO) (4.5% oxirane content) was prepared in our laboratory as described in a previous communication [11]. The barium, cadmium, calcium and zinc soaps of rubber seed oil used in this study were prepared by metathesis in aqueous alcohol as described previously [12].…”
Section: Methodsmentioning
confidence: 99%
“…These includes epoxidation with percarboxylic acid generated in situ in the presence of acids or enzymes as catalysts [14], epoxidation with organic and inorganic oxidants such as potassium peroxomonosulphate, meta-chloroperoxybenzoic acid and ethyl methydioxirane [15,16], epoxidation with halohydrins for the epoxidation of olefins with electron-deficient double bonds and epoxidation with molecular oxygen [17]. From process, environmental safety and efficiency point of view epoxidation of vegetable oils in one step, i.e., with peroxy acid generated in situ from carboxylic acid (formic/acetic acid) with hydrogen peroxide in the presence of acid catalyst is widely used on an industrial scale.…”
Section: Introductionmentioning
confidence: 99%